Combined Transcriptomic and Metabolomic Analyses Reveal the Mechanisms by Which the Interaction Between Sulfur and Nitrogen Affects Garlic Yield and Quality - Licai Ren; Xudong Pan; Yang Deng; Zhengkang Ge; Shiyuan Li; Dong Su; Guoqian Zhao; Hui Tang; Xiangfei Wang (Horticulturae)
Nitrogen and sulfur are essential macronutrients in plant growth and development, and their interaction profoundly influences gene expression, metabolic activities, and adaptability in plants, directly affecting plant growth and yield. Garlic (Allium sativum L.) is a crop of significant economic and medicinal value. However, despite the critical role of the nitrogen–sulfur interaction in garlic’s adaptability, yield, and quality, the specific mechanisms underlying these effects remain unclear. In this study, transcriptomic and metabolomic analyses were employed to investigate the effects of combined sulfur and nitrogen application on garlic bulb tissues. The results show that the combined application of sulfur and nitrogen significantly increased the diameter and weight of garlic bulbs by 14.96% and 35.47%, respectively. The content of alliin increased by 28.48%, while the levels of abscisic acid (ABA), jasmonic acid (JA), salicylic acid (SA), and gibberellin (GA) increased by 15.82%, 12.94%, 32.34%, and 48.13%, respectively. Additionally, the activities of alliinase, superoxide dismutase (SOD), and catalase (CAT) were enhanced by 7.93%, 4.48%, and 19.74%, respectively. Moreover, the application of sulfur and nitrogen significantly reduced the malondialdehyde (MDA) content and peroxidase (POD) activity in garlic bulbs by 29.66% and 9.42%, respectively, thereby improving garlic’s adaptability and growth potential. Transcriptomic analysis revealed differentially expressed genes in several key pathways, including plant hormone signal transduction, RNA degradation, glutathione metabolism, amino acid biosynthesis, and glycerophospholipid metabolism. Metabolomic analysis identified 80 differentially abundant metabolites primarily consisting of amino acids, indole carboxylic acids, and fatty acids. The integrated transcriptomic and metabolomic analyses highlighted the pivotal roles of glutathione metabolism, glycerophospholipid metabolism, and amino acid biosynthesis pathways in the synergistic effects of sulfur and nitrogen. This study not only provides critical scientific evidence for understanding the mechanisms underlying the nitrogen–sulfur interaction’s impact on the yield and quality of garlic but also offers a scientific basis for optimizing nutrient management strategies to enhance garlic yield and quality.